Sustainable growth with pollution augmenting technological changes - Yoon, Sang Won; Yoon, Chang-Ho (2023)
Disruptive technological changes, including carbon capture and storage, can have macroeconomic rebound effects that pose a threat to long term environmental sustainability when not accompanied by pollution taxes. The paper demonstrates that when the elasticity of intertemporal substitution is less than one, implementing a Pigouvian tax effectively stabilizes pollution emissions, regardless of technical and consumption elasticities of substitution. However, if the elasticity of intertemporal substitution exceeds one, flexibility in technical or consumption substitution could cause sustainable growth to falter. The policy implications concerning the role of subsidies for clean technology are discussed.
Keywords: Elasticity of intertemporal substitution; Optimal pollution tax; Sustainable development; dept.eco; energy rebound; technological change

International comparison on economics impact from the COVID-19 pandemic: policy analysis - Supple, Brandon; Yu, Jia (Medical Research Archives, 2023)
Keywords: SCSU-student; dept.eco; peer-reviewed

Unlocking Opportunities for Migrant Workers in China: Analyzing the Impact of Health Insurance on Hukou Switching Intentions - Chen, Hong; Yu, Jia; Qin, Mingshuai; Wang, Yangyang; Qin, Lijian (Sustainability, 2023)
The Chinese urban–rural binary health insurance structure has contributed to a significant urban–rural segmentation and regional fragmentation, which will affect labor mobilization and urbanization. The purpose of this research is to study whether and how urban–rural binary health insurance impacts the intentions of migrant workers to switch between rural and urban hukou. Pooled data were drawn from China Migrants Dynamic Survey, collected by the National Health Commission of China. The study applied the instrument variable model due to the existence of the endogeneity; and the IVprobit model to conduct the empirical analysis. Our findings are as follows: (1) the urban–rural binary health insurance affects migrant workers’ intentions to switch to urban hukou significantly. (2) The negative impact of originally rural health insurance on migrant workers’ intention of switching to urban hukou is relatively large for low-education-level migrant workers. (3) Compared with new generation of migrant workers, old migrant workers have higher health insurance dependency levels. Finally, our research suggested several policy implications, such as accelerating the establishment of a unified urban–rural health insurance system, increasing the urban health insurance participation rate of migrant workers in their working cities, and including migrant workers in the scope of equal access to urban public services, etc. All the policy suggestions are essential in order to accelerate the citizenization of migrant workers, improve the quality of urbanization, and promote the construction of a unified national labor market.
0 citations (Crossref) [2023-10-31] Number: 8
Keywords: dept.eco; intention of switching to urban hukou; migrant workers; peer-reviewed; urban–rural binary health insurance